The Effect of Nutrient Deprivation on Markers of Oxidative Stress, Inflammation, and Transcriptome in Normal and Type-2 Diabetic Human Skeletal Muscle Myoblasts - Lael Ceriani; Daniel E. Newmire; Xavier F. Gonzales; Jean Sparks; Jose Guardiola; Felix O. Omoruyi (Journal of Nutrition and Metabolism)
Conclusions: Myoblast viability and density were lower in the nutrient-deprived conditions and in the FBS compared to the HS serum. The biomarker of oxidative stress was lower in the serum concentration in a scaled effect, yet higher in HS. The biomarker of inflammation was higher in the HSMM cell line, shorter incubation time period, and in FBS. HS used as a media may supply nutrients and hormonal confounders that may support or stress myoblast growth.